2015
DOI: 10.1016/j.virusres.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids substitutions in σ1 and μ1 outer capsid proteins of a Vero cell-adapted mammalian orthoreovirus are required for optimal virus binding and disassembly

Abstract: In a recent study, the serotype 3 Dearing strain of mammalian orthoreovirus was adapted to Vero cells; cells that exhibit a limited ability to support the early steps of reovirus uncoating and are unable to produce interferon as an antiviral response upon infection. The Vero cell-adapted virus (VeroAV) exhibits amino acids substitutions in both the σ1 and μ1 outer capsid proteins but no changes in the σ3 protein. Accordingly, the virus was shown not to behave as a classical uncoating mutant.In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Indeed, we have previously observed that a 1 variant contains different levels of particle-associated 1 (76). Another study has also suggested that compatibility between 1 and 1 confers optimal 1 encapsidation and function on the particle (70). The difference in 1 encapsidation between T3D F and T3D C may be governed by the function of 1 or yet another protein.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, we have previously observed that a 1 variant contains different levels of particle-associated 1 (76). Another study has also suggested that compatibility between 1 and 1 confers optimal 1 encapsidation and function on the particle (70). The difference in 1 encapsidation between T3D F and T3D C may be governed by the function of 1 or yet another protein.…”
Section: Discussionmentioning
confidence: 91%
“…Since both the attachment and ISVP* phenotype of T3D F /T3D C S1 could be explained by 1-2 interaction, we decided to determine whether a mismatch between T3D C 1 and T3D F 2 accounts for the phenotypes observed. The 2 proteins of T3D F and T3D C differ at residue 504, resulting in a glycine-to-glutamate change, and at residue 509, resulting in a glycine-to-arginine change (70). Thus, to test our idea about the contribution of 1-2 mismatch, we generated two additional viruses, T3D F /T3D C L2 (a monoreassortant that contains an L2 gene segment from strain T3D C in an otherwise T3D F background) and T3D F /T3D C S1L2 (a double reassortant that contains both the S1 and L2 gene segments from strain T3D C in an otherwise T3D F background).…”
Section: Figmentioning
confidence: 99%
“…Finally, reovirus is a promising contender for virus-mediated tumor oncolysis. We and others have found that genetic modification of reovirus can improve oncolytic activity in vitro and in animal cancer models (87)(88)(89)(90)(91). Reovirus also provides a potential vaccine vector (92,93).…”
Section: Discussionmentioning
confidence: 99%
“…For example, many reovirus protein functions have been characterized by comparing phenotypes among natural reovirus variants, reovirus genome reassortants, and laboratory derived reovirus mutants10111213141516171819. In conjunction with reverse genetics approaches for these viruses202122232425, it is now possible to design copious virus mutants, purify them in-slurry, and make rapid comparisons of virus proteins, virion structure, and virus replication.…”
Section: Discussionmentioning
confidence: 99%